Implementasi Sistem Pengajuan dan Penjadwalan Mobil Operasional Berbasis Web Untuk SPPD pada PT. Setya Kuliner Mandiri - Muhammad Andika Frasetya; Genta Davida Prinandio; Khairur Ramadhan; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
This internship program was conducted at PT Setya Kuliner Mandiri, focusing on the implementation of a web-based operational vehicle application and scheduling system to support the official travel process (SPPD). The background to this activity stems from administrative issues that are still carried out manually, such as recording in agenda books, communication via text messages, and the absence of a centralized database that causes vehicle schedule conflicts, miscommunication with drivers, and a lack of documentation of vehicle usage history. The purpose of this activity is to help the company realize a more efficient, transparent system that is able to provide real-time information regarding SPPD applications, vehicle availability, and driver assignments. The partner in this activity is the company's Operational Administration department, which is the main unit in managing SPPD and operational vehicles. The methods used include observation, interviews, literature studies, and system design using the SDLC approach. The results of this activity indicate that the web-based system is able to reduce the risk of recording errors, improve coordination between units, and provide a neater and more easily traceable digital archive. These findings emphasize the importance of digital transformation for companies to improve operational effectiveness and support more accurate decision making.